2002
DOI: 10.1016/s0893-133x(02)00341-x
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Increases Phosphorylation of Extracellular Signal-regulated Kinase and Transcription Factors in the Rat Striatum via Group I Metabotropic Glutamate Receptors

Abstract: Amphetamine is an indirect dopamine receptor agonist and increases glutamate release in the striatum. Activation of group I metabotropic glutamate receptors (mGluRs) upregulates cAMP response element-binding protein (CREB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 39 publications
4
106
0
2
Order By: Relevance
“…Moreover, short-term cocaine potentiates synaptic responses in ventral tegmental area dopamine neurons by promoting the rapid insertion of surface glutamate receptors (Borgland et al, 2004;Sun et al, 2008;Ferrario et al, 2011). ERK1/2 activation is also observed after amphetamine injections (Choe et al, 2002), and this requires both D1Rs and NMDARs (Valjent et al, 2005). The amphetamine-induced phosphorylation of ERK1/2 requires PKA-mediated phosphorylation of DARPP-32 and its subsequent inhibition of PP1 (Fig.…”
Section: G Drugs Of Abusementioning
confidence: 88%
“…Moreover, short-term cocaine potentiates synaptic responses in ventral tegmental area dopamine neurons by promoting the rapid insertion of surface glutamate receptors (Borgland et al, 2004;Sun et al, 2008;Ferrario et al, 2011). ERK1/2 activation is also observed after amphetamine injections (Choe et al, 2002), and this requires both D1Rs and NMDARs (Valjent et al, 2005). The amphetamine-induced phosphorylation of ERK1/2 requires PKA-mediated phosphorylation of DARPP-32 and its subsequent inhibition of PP1 (Fig.…”
Section: G Drugs Of Abusementioning
confidence: 88%
“…For example, we have shown that AMPH inhibits serine/threonine kinase Akt/protein kinase B (Garcia et al, 2005), and this might simply require intracellular AMPH and not DAT activity per se. Moreover, AMPH has been shown to activate extracellular signal-regulated kinase 1/2 (Choe et al, 2002) and PKC (Giambalvo, 1992a,b) and might directly modulate the activity of intracellular signal transduction cascades to regulate DAT membrane expression.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has revealed that acute psychostimulant administration increases pERK and pCREB (Choe et al, 2002), and although any accompanying change in āŒ¬FosB is minimal, āŒ¬FosB is resistant to metabolism and is thus relatively more persistent (Nestler, 2004). With repeated injections, pERK and pCREB normalize or potentially "overcompensate" by decreasing levels, whereas āŒ¬FosB accumulates in brain tissue (Nestler, 2004).…”
Section: Downloaded Frommentioning
confidence: 99%